Ethnobotany Bua-Bua: Foodstuff and Medical - Baguna, Firlawanti Lestari; Tamnge, Fadila; Kaddas, Fatmawati (Jurnal Pertanian Khairun, 2024)
Bua-Bua people utilize plants as traditional medicines in forest areas. It is easy to find simple to process. The study goals are to describes the knowledge of the Bua-Bua community to using plants as medicine and plants utilization as traditional medicines and how to process medicinal plants in Bua-Bua village. The observation method used is qualitative with a descriptive analysis approach. The data collection was done by observation and semi-structured interviews with key informants. Determination of key informants is done by the snowball technique. Data collected in the form of primary data and secondary data. Primary data is related to the use of medicinal plants and medicinal plants. The interview results showed that there were 46 types of plants that were used to treat various types of diseases commonly suffered by the people of Bua-Bua Village. Commonly used plants as medicine include cinnamon, nutmeg, ketapang, noni, soursop, mangosteen, avocado, candlenut, lemongrass, cat whiskers, betel, gofasa, mayana, kencur, star fruit, angsana, yellow, greetings, and 7 types other unknown scientific names are ngoyo, yellow root , giha, galala, ligagamo, saiyo, utulage and firoro. Due to time constraints, 7 species of plants were not identified. These plants are obtained from forest areas and around forest areas. How to use plants that have medicinal motley begin by boiling, grinding, burning and mashed fruit, eat directly, and soak in water. The benefits of plants that are utilized by Bua-Bua people generally can treat various diseases that are often suffered by the community such as malaria, stomach ulcers, fever, diarrhea, hypertension, anemia, mild strokes, and various other diseases.